Integration of WiMAX and WiFi optimal pricing for bandwidth sharing. - Niyato, Dusit; Hossain, Ekram
Broadband wireless access networks based on WiMAX can provide backhaul support for mobile WiFi hotspots. We consider an integrated WiMAX/WiFi network for such an application where the licensed WiMAX spectrum is shared by the WiFi access points/routers to provide Internet connectivity to mobile WiFi users. The WiMAX backbone network and WiFi hotspots are operated by different service providers. Issues such as protocol adaptation, quality of service support, and pricing for bandwidth sharing that are related to integration of these networks are discussed. In addition, we propose a model for optimal pricing for bandwidth sharing in an integrated WiMAX/WiFi network. A Stackelberg leader-follower game is formulated to obtain the optimal pricing solution for bandwidth sharing. Performance evaluation results reveal some interesting insights into the problem.
Keywords: Internet connectivity; WiFi access points-routers.; Bandwidth sharing; Broadband wireless access networks; Integrated WiMAX-WiFi network; Leader-follower game; Mobile Wifi hotspots; Pricing; Protocol adaptation; Quality of service